Postawa twórcza a style radzenia sobie ze stresem młodzieży uzdolnionej artystycznie = Creative attitude and the styles of coping with stress among artistically-talented young people - Kuśpit, Małgorzata (Zielona Góra: Lubuskie Towarzystwo Naukowe)
The article focuses on the relationship between creative attitude and the styles of coping with stress among artistically-talented young people. It turns out that success in achieving intended goals depends not only on intellectual potential, but also on environmental factors and personality characteristics. The uniqueness and uncommonness of artisticallytalented individuals, their high expectations for themselves, and well as demands from their surroundings can lead to stress.
Keywords: postawa twórcza; style radzenia sobie ze stresem; uzdolnienia plastyczne; creative attitude; styles of coping with stress; artistic talents